Noninvasive assessment of dermal carotenoids as a biomarker of fruit and vegetable intake(1)(2)(3) - Mayne, Susan T (American Society for Nutrition, 2010)
Background: Resonance Raman spectroscopy (RRS) has been suggested as a feasible method for noninvasive carotenoid measurement of human skin. However, before RRS measures of dermal carotenoids can be used as a biomarker, data on intra- and intersubject variability and validity are needed. Objective: The purpose of this study was to evaluate the reproducibility and validity of RRS measures of dermal total carotenoids and lycopene in humans. Design: In study 1, 74 men and women with diverse skin pigmentation were recruited. RRS measures of the palm, inner arm, and outer arm were obtained at baseline, 1 wk, 2 wk, 1 mo, 3 mo, and 6 mo (to maximize seasonal variation). The RRS device used visible light at 488 nm to estimate total carotenoids and at 514 nm to estimate lycopene. Reproducibility was assessed by intraclass correlation coefficients (ICCs). In study 2, we recruited 28 subjects and assessed dietary carotenoid intake, obtained blood for HPLC analyses, performed RRS measures of dermal carotenoid status, and performed dermal biopsies (3-mm punch biopsy) with dermal carotenoids assessed by HPLC. Results: ICCs for total carotenoids across time were 0.97 (palm), 0.95 (inner arm), and 0.93 (outer arm). Total dermal carotenoids assessed by RRS were significantly correlated with total dermal carotenoids assessed by HPLC of dermal biopsies (r = 0.66, P = 0.0001). Similarly, lycopene assessed by RRS was significantly correlated with lycopene assessed by HPLC of dermal biopsies (r = 0.74, P < 0.0001). Conclusion: RRS is a feasible and valid method for noninvasively assessing dermal carotenoids as a biomarker for studies of nutrition and health.